Lipid Droplet, a Key Player in Host-Parasite Interactions - Vallochi, Adriana Lima; Teixeira, Livia; Oliveira, Karina da Silva; Maya-Monteiro, Clarissa Menezes; Bozza, Patricia T. (Frontiers in Immunology, 2018)
Lipid droplets (lipid bodies, LDs) are dynamic organelles that have important roles in regulating lipid metabolism, energy homeostasis, cell signaling, membrane trafficking, and inflammation. LD biogenesis, composition, and functions are highly regulated and may vary according to the stimuli, cell type, activation state, and inflammatory environment. Increased cytoplasmic LDs are frequently observed in leukocytes and other cells in a number of infectious diseases. Accumulating evidence reveals LDs participation in fundamental mechanisms of host-pathogen interactions, including cell signaling and immunity. LDs are sources of eicosanoid production, and may participate in different aspects of innate signaling and antigen presentation. In addition, intracellular pathogens evolved mechanisms to subvert host metabolism and may use host LDs, as ways of immune evasion and nutrients source. Here, we review mechanisms of LDs biogenesis and their contributions to the infection progress, and discuss the latest discoveries on mechanisms and pathways involving LDs roles as regulators of the immune response to protozoan infection.